Hematological Markers in the Assessment of Severity of COVID-19 Infection—A Retrospective Cross-Sectional Study - Swathy Moorthy; Teena Koshy; Mahesh Kumar K; Jasmine Chandra A; Emmanuel Bhaskar; Santhi Silambanan (Journal of Health Sciences and Surveillance System, 2022)
Background: Patients with COVID-19 (coronavirus disease 2019) present varying disease severity; with such heterogeneity in clinical presentations, it can be challenging to assess the severity and progression of the disease. In addition, no specific markers have been identified that would indicate the diagnosis or prognosis of the disease. Therefore, this study was aimed to determine whether a panel of hematological and inflammatory biomarkers were indicative of disease severity in the assessment and the prognosis of COVID-19. Methods: The retrospective cross sectional study was carried out in a university hospital in South India between May 2020 and September 2020. The participants were 997 patients with COVID-19, confirmed by real-time reverse transcriptasepolymerase chain reaction (RT-PCR). Information regarding demographics and laboratory tests was obtained from medical records. Association analysis was conducted using SPSS, version 16, and a P-value <0.05 was considered statistically significant. Results: Inflammatory markers such as C-reactive protein (CRP) and D-dimer, calculated inflammatory ratios, and hemoglobin were significantly increased in cases of severe COVID-19. Leucocytosis with increased absolute neutrophil count and decreased absolute lymphocyte count were observed. Conclusion: Haematological and inflammatory markers mayindicate the severity of the disease. The severity of COVID-19 was indicated by elevated total white cells, increased neutrophillymphocyte, and platelet–lymphocyte ratios. Increasing levels of CRP indicated a severe prognosis of the disease. D-dimer elevations may indicate the incidence of thromboembolic episodes. Therefore, hematological indices were considered applicable in assessing the progression of the disease and for the risk stratification of the disease.